The Scope Of UNHCR Protection For Women And Children - عثمان, سلمان; محرز, هيا (Latakia University Journal - Economic and Legal Sciences Series, 2021)
It was necessary for the United Nations to respond to the feeling of the international community and to give a new and direct role for the benefit of the refugee category, In 1949, the High Commissioner for Refugees was established as a special-purpose organization, as its protection extended to all refugees, regardless of their place of origin or nationality, as its work is of a humanitarian and social nature and not political. Today, the organization has become an effective and positive role in providing international protection for refugees, by searching for permanent solutions to their problems. The refugee problem is an international responsibility, and countries alone cannot shoulder their economic and social burdens